Addressing the need for genetic cancer risk assessment in Mexico: From establishment of a formal program to delivery innovation and expansion - Yanin Chávarri-Guerra; José Luis Rodríguez-Olivares; Alfredo Ramírez-González; José Manuel Moreno-Mirón; Alex Lagunas-Medina; José Carlos Peñafort-Zamora; Jazmin Arteaga-Vázquez; Gregorio Quintero-Beuló; Roberto Sánchez-Reyes; Jeffrey N. Weitzel (Genetics in Medicine Open)
Purpose: The purpose of this manuscript is to show the process of the establishment and adaptation of an oncogenetics program in Mexico. Methods: The oncogentics program at the Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán was established as a traditional in-person service and adapted to include telemedicine counseling to expand services to other hospitals and persists as a mixed counseling model with research/commercial genetic testing. Results: A total of 2222 participants were included with a median age of 47 years and 77.6% were women; 64% and 36% were enrolled in person and by phone, respectively; 91.1% had research testing, 4.7% commercial testing, 2% complementary pharma testing, and 2.1% had more than 1 testing. Results disclosure was by phone for 49.6%, in person for 43.3%, and by videocall for 7.1% of the cases. Cascade testing proportion was similar in both groups (88%), and 14.8% probands and 40.8% family members had a positive result for a pathogenic cancer susceptibility gene variant. Conclusion: Our results demonstrated that genetic cancer risk assessment is feasible in limited resources settings and provide evidence that telemedicine is effective and can be used as an alternative in real-world populations. Our model could be adapted and potentially replicated in other institutions and countries that face similar barriers for health care.